1977
DOI: 10.1111/j.1471-0528.1977.tb12555.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Human Placental Lactogen Profiles Over 24 Hours in Normal and Diabetic Pregnancy

Abstract: Summary Plasma human placental lactogen (HPL) concentrations have been measured at frequent intervals over 24 hours in 24 normal women, 13 chemical and 13 insulin dependent diabetic patients during the third trimester of pregnancy. Most of the women studied displayed variation in HPL levels during the day, but there was no evidence of a diurnal rhythm, nor significant changes following meals or during the nocturnal fast. The mean plasma HPL concentrations over 24 hours in the chemical and insulin dependent dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
(6 reference statements)
1
13
0
Order By: Relevance
“…4). 148 Luthman/Stock/Wemer/Bremme GH and GHBP during Pregnancy Pituitary GH and PL in plasma were inversely corre lated in all women supporting the hypothesis that PL exerts an inhibitory effect on pituitary GH [28], In con trast, PL was positively correlated to PRL in the GDM group and in the two groups together. Furthermore, PL was inversely correlated to GHBP in all women.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…4). 148 Luthman/Stock/Wemer/Bremme GH and GHBP during Pregnancy Pituitary GH and PL in plasma were inversely corre lated in all women supporting the hypothesis that PL exerts an inhibitory effect on pituitary GH [28], In con trast, PL was positively correlated to PRL in the GDM group and in the two groups together. Furthermore, PL was inversely correlated to GHBP in all women.…”
Section: Discussionsupporting
confidence: 49%
“…The levels of PRL and PL did not vary significantly during the tolerance tests. Lack of variation in PL levels has pre viously been reported during an oral glucose tolerance test in healthy pregnant women and women with GDM [28], GHBP was higher in the GDM group compared to the control group. The increased GHBP levels in the women with GDM were apparently a consequence of increased BMI in these women and not of the GDM state per se.…”
Section: Discussionmentioning
confidence: 95%
“…Using a 6 hourly sampling protocol in sheep, Chan et al (1978) found little variation in PL concentrations in late pregnancy. However, recent studies suggest that concentrations of human PL are not as stable as was formerly thought, rapid changes of up to twofold occurring in some patients (Pavlou, Chard & Letchworth, 1972;Lindberg & Nilsson, 1973;Vigneri, Squatrito, Pezzino, Cinquerui, Proto & Montoneri, 1975;Gillmer, Beard, Oakley, Brooke, Brudenell & Chard, 1977). The cause of variations in concentrations of PL in the circulation is unknown.…”
Section: Discussionmentioning
confidence: 93%
“…Thus fasting and hypoglycemia bring about a rise in HPL levels, while hyperglycemia causes a fall (5, 8, 19, 24). In normal or diabetic women in the third trimester of pregnancy other investigators have been unable to demonstrate changes in HPL levels corresponding to changes in blood glucose, when the latter are brought about by oral glucose tolerance tests (6,9).…”
Section: Discussionmentioning
confidence: 99%